Dental Treatment and Oral Rehabilitation for Adults With Intellectual Disability Under General Anesthesia. Issue 4 (21st May 2021) - Mastilovic, Gorana; Petrovic, Bojan; Peric, Tamara; Pantelinac, Jelena; Markovic, Evgenija; Markovic, Dejan
Abstract: Background: Oral healthcare of adults with intellectual disabilities (ID) presents one of the most unattended health needs, while at the same time, having a huge impact on their quality of life. Specific Aims: The aims of the present investigation were to assess the rate of tooth loss and the influence of tooth extractions during dental procedures under general anesthesia (GA) on the prospects for efficient oral rehabilitation of adults with ID in Serbia. Methods: This study was designed as a retrospective observational study, based on available data from dental, medical and anesthesia records. The pattern of oral healthcare and rehabilitation possibilities of 257 adults with ID who were treated under GA was investigated. Distribution of restored and extracted teeth, and demand for prosthodontic rehabilitation were analyzed. Findings: The average number of dental appointments under GA in 10 years of observation period was 1.36 ± 0.79, with 3.64 ± 4.42 restored teeth and 6.64 ± 5.95% extracted teeth. Prosthodontic treatment was provided for 29 (11.28%) patients. The analysis identified that age ( p = 0 .041) and number of dental visits ( p = 0.002) were significant predictors for prosthodontics rehabilitation. Conclusion: Age, level of IQ, and the presence of concomitant conditions in adults with ID could be considered as a predictor for tooth loss. Regular attendance to dental treatment was identified as a manner for successful oral rehabilitation. Patient‐centered individualized approach, implementation of preventive protocols, and improvement in delivering prosthodontic rehabilitation are mandatory in providing dental care for persons with ID.